(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2020)
The conference paper addressed by Marvin Carlson in October 2019 at Unirio, whose translation I present here, examines a significant subject for those who study theatrical reception. Leading the reader through different productions and various theatre groups throughout history, the author discusses and proves that, due to certain unique characteristics of theatre as a human activity, this art operates a universal dynamic of cognition, based on the memory of previous experiences juxtaposed with the new ones. The author calls this process ghosting.